Risk Analysis of Pesticide Exposure Associated with Reduced Cholinesterase Levels in Indonesian Farm Workers: A Meta-Analysis - R Azizah; Juliana Jalaludin; Muhammad Addin Rizaldi; Globila Nurika; Mochammad Sholehhudin; Zaneta Aaqilah Salsabila; Zafira Nuha Naura (Faculty of Public Health, Hasanuddin University, Makassar, 2025)
Pesticide exposure remains a major occupational health problem, with the World Health Organization (WHO) reporting between 1 and 5 million cases of pesticide poisoning annually among agricultural workers. This study aimed to analyze the risk factors associated with pesticide poisoning by conducting a meta-analysis of published research. The meta-analysis was performed in four stages: data abstraction, statistical analysis using JASP Version 0.18.3, heterogeneity testing, and publication bias assessment. The random-effects model was applied to the variables of Personal Protective Equipment (PPE) use and length of work, as the heterogeneity test indicated significant variation between studies (p = 0.001). In contrast, the fixed-effects model was used for individual hygiene (p = 0.006). Egger’s test showed no indication of publication bias for PPE use (p = 0.356) and length of work (p = 0.395). The results revealed that PPE use increased the risk of decreased cholinesterase levels by 1.584 times, poor individual hygiene by 1.954 times, and working more than 5 hours by 1.665 times. In conclusion, individual hygiene was identified as the most significant risk factor. Farmers who neglect personal hygiene practices, such as bathing after spraying or changing clothes immediately, face a substantially greater risk of reduced cholinesterase levels due to pesticide poisoning.